Rapid decline of fasting glucose in HCV diabetic patients treated with direct-acting antiviral agents. (May 2016) - Pavone, P.; Tieghi, T.; d'Ettorre, G.; Lichtner, M.; Marocco, R.; Mezzaroma, I.; Passavanti, G.; Vittozzi, P.; Mastroianni, C.M.; Vullo, V.
Abstract: Association between hepatitis C virus (HCV) infection and diabetes has been widely postulated. Little is known about the effect of direct-acting antiviral agents (DAAs) on glycaemic control. The aim of our study was to evaluate the glycaemic control modifications in a case series of HCV-positive diabetic patients receiving DAAs. We retrospectively evaluated 149 HCV-positive patients in two different institutions affiliated with Sapienza University: Policlinico Umberto I of Rome and Ospedale Santa Maria Goretti of Latina. We were able to identify 29 patients with type 2 diabetes mellitus (19% of total population) who were receiving different interferon-free regimens. During-treatment fasting glucose (FG) values were available for 21 patients, and analysis revealed a statistically significant reduction (p 0.007); reduction mean value was −52.86 mg/dL. A glycated haemoglobin (A1C) value during treatment (at weeks 4, 8 and/or 12) was available for ten patients, and the analysis revealed a statistically significant reduction (p 0.021) with a reduction mean value of −1.95%. Six patients (23%) needed to reduce hypoglycaemic drugs, eight of ten patients showed reduction of A1C and 14 (67%) of 21 patients showed reduced FG during treatment. FG and A1C reductions values were independent from which DAA was present in the regimen, HCV genotype, body mass index and HIV status. In order to avoid hypoglycaemic events, diabetic patients receiving DAAs should be closely monitored for reduction of hypoglycaemic drugs. Furthermore, in our opinion, diabetes could be considered as an element to prioritize treatment in those patients with no apparent liver disease.